Euphrasia taurica Ganesch. ex Popl. in the Crimean flora (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Micro- and macro morphology of vegetative (stems, leaves) and generative (inflorescences, flowers, fruits and seeds) organs of Euphrasia taurica Ganesch. ex Popl. were studied. Its distributional, phytocoenotic and ecological features of this Crimean endemic species were studied and mapped. It is determined, that E. taurica grows the rocky slopes, yailas in rare plant communities of Junipereta hemisphaericae and Cariceta humilis. The conditions of some populations of this species were studied. Some of them have decreasing number and density of plants of its populations last years. This species is recommended to include in Red Data Book of Ukraine.
Keywords: Euphrasia taurica Ganesch. ex Popl., morphological characteristics, chorology, phytocoenotic features.